A study of sexual related determinants and marital quality among married couple in Malaysia - Ong, Joo Yee; Pang, Rebecca Sing Vun; Tan, Jing Zhi (2018)
Divorce rate had been increasing dramatically in Malaysia over the past few years. One of the main reason was low level of marital quality. Hence, present study determined to examine the mediation effects of sexual satisfaction on sexual desire and compatibility towards marital quality among married individuals in Malaysia. Moreover, this study also aimed to study the moderation effect of marriage length on sexual satisfaction towards marital quality among married individuals in Malaysia. 302 participants who had registered under National Registration Department of Malaysia had participated our study. This study was a quantitative, cross-sectional, and also correlational study. Present study was using online survey method and purposive sampling methods to collect primary data. The results depicted that sexual satisfaction and compatibility significantly affected marital quality. Besides, results also showed that sexual satisfaction significantly mediated the effect of sexual desire and compatibility towards marital quality. However, results of this study indicated that the moderation effect of marriage length on sexual satisfaction towards marital quality was not significant. In a nutshell, marital counsellors and practitioners could put sexual discontentment or dissatisfaction as one of the reason that affected low marital quality of clients as sex-related behaviours or desires might be the factors that were affecting marital relationships of married couples in Malaysia.